A National Survey of Antimicrobial Prophylaxis in Adult Cardiac Surgery Across Canada - Fran L Paradiso-Hardy; Patti Cornish; Chantal Pharand; Stephen E Fremes (Canadian Journal of Infectious Diseases)
OBJECTIVE: To characterize national and regional patterns of antimicrobial prophylaxis in adult cardiac surgery across Canada.